THE INCOMMUNICABLE NATURES OF GOD: A BIBLICAL UNDERSTANDING - Reymand M. Hutabarat (Jurnal Koinonia, 2015)
God has some basic attributes that make Him different from angels,human beings and all others created beings. There are six divine attributeswhich belong to God Himself and cannot be communicable to other being. Theyare: Omnipresence, Omniscience, Omnipotence, Immutability, Self existence,and Eternal. The result of this study shows that God is present everywhere inHis creation. The unchangeable nature of God guarantees that what He hasproposed will be fulfilled by Him, for it is impossible for Him to lie; The everpresent nature of God assures His people of His continued accompaniment to betheir “help and shield;” His eternal and all-powerful nature assure His people ofHis power to raise the dead from the graves and to give them eternal life, thatthey will never die; The all-knowing, all-powerful, ever-present , unchangeable,and eternal natures of God assure His people of their present needs and of theirwelfare in the world to come; Only “he who believes in the Son has eternal life;but he who does not obey the Son, shall not see life, but the wrath of God abideson him.